Minimum Wages, Economic Growth and Human Development Index on Unemployment in East Java - Redy Eko Hari Suprapto; Kharis Marpurdianto; Sugeng Widodo (Budapest International Research and Critics University, 2022)
The larger the workforce, the very low wages received by the workers, the low level of the economy and the low human development index, the more difficult it is for people to find work. This is a problem that needs to be resolved immediately.The purpose of the study is that the Minimum Wage, Economic Growth and Human Development Index have a joint impact on the number of unemployed in East Java Province and to find out the Minimum Wage, Economic Growth and Human Development Index have an individual impact on the number of unemployed in East Java. The sample used was secondary data from the East Java BPS relating to the variables analyzed from 2017-2021. Minimum Wage, Economic Growth and Human Development Index both together have a significant impact on the Number of Unemployment in East Java Province. Minimum wages and economic growth have a significant impact on unemployment in East Java Province.